Effects of aquatic and land high-intensity interval trainings on selected bio- and physiological variables among obese adolescents - Liao, Ting; Zheng, Chuanbo; Xue, Jungang; Wang, Yong “Tai” (Frontiers in Endocrinology, 2024)
Background: Obesity among adolescents have become a global public health problem. Exercises can effectively improve the bio-physiological factors of obese adolescents. High-intensive interval training (HIIT) has been applied to obese adolescents. Studies have reported that the Aquatic environment may bring the same or more positive exercise effects as the land environment. Therefore, the purpose of this study was to examine the effects of aquatic and land interventions on selected bio-and physiological variables among obese adolescences.Methods: Twenty-eight obese adolescents who met the requirements participated in and completed this study. The participants were randomly assigned to Aquatic HIIT group (n=17) or Land HIIT group (n=11) for a four-week exercise intervention, 3 time/week. Each Intervention program was one-hour long, including 20 minutes of warm-up, 30 minutes of HIIT and 10 minutes of stretching and relaxation. Bio-and physiological variables including Anthropometry and body composition, Physical Function and blood pressure, and Lipid metabolism indexes were collected before and after the Aquatic and Land interventions.Results: After four weeks of exercise interventions, the body mass, BMI, body fat rate, waist circumference, hip circumference and body water content were significantly reduced (p<0.05), and the lean body mass were significantly increased (p<0.05) in both groups. Both group exhibited significant effects in decreasing, systolic blood pressure (p<0.05), diastolic blood pressure (p<0.01), and increasing vital capacity and total energy consumption (p<0.05). The Aquatic HIIT group showed significant effects on reducing Rest heart rate (p<0.05), but no significant changes in Rest heart rate in Land HIIT group (p=0.364). The low-density lipoprotein cholesterol in both groups was significantly decreased (p<0.05). Moreover, the Aquatic HIIT group had significant better improvements (p<0.05) in lean body mass, waist circumference, waist-to-hip ratio, vital capacity and total energy consumption than Land HIIT group did.The results of the present study demonstrated that in a short-term (4 weeks) both Aquatic and Land HIIT interventions may improve the body composition, physical function, blood pressure and low-density lipoprotein cholesterol (LDL-C) of overweight and obese adolescents. Furthermore, the Aquatic HIIT may be superior than the Land HIIT in weight control among the obese adolescents.